181k views
2 votes
Problem: -4(6-y)+4=-4

Step 1: -24-4y+4=-4
Step 2: -20-4y=-4
Step 3: -4y=16
Step 4: y=-4

What step was the mistake made?
What is the correct solution?

2 Answers

5 votes

step one and two is wrong because when you're distributing this equation u should get -24+4y+4=-4 u caculate and then u move the constant to the right side and caculate again then divide

User Bhuvanesh BS
by
6.2k points
2 votes
Step 2 is wrong and i don't know the other question
User Andrew Hershberger
by
5.5k points